Tundish stuffing sand and preparation method thereof
By using tundra drainage sand made of magnesite sand and other materials, the problems of liquid steel pollution and equipment damage in the flow-controlled casting method of plug-free rods are solved, and the effects of high automatic casting rate and low pollution are achieved, and the steel billets are improved Quality and equipment life.
Patent Information
- Application Number
- CN202411446393.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-16
- Publication Date
- 2025-01-10
AI Technical Summary
In the existing plug-in-controlled flow casting method, the protective slag or drainage sand filled in the fixed diameter outlet is easily sintered at high temperatures, resulting in the inability to flow out automatically, resulting in liquid molten steel pollution and equipment damage, and the use of asbestos ropes has safety risks. and environmental pollution problems.
Using tundra drainage sand made of magnesite sand, dolomite sand, raw perlite, cyanite and rare earth powder, produces lightweight, porous materials and reduces steel by heat treatment during tundra baking and steel storage. Fluid erosion and sintering to improve the automatic casting rate and reduce liquid molten steel pollution through a stable coating of rare earth ore powder.
It improves the automatic pouring rate of the tundra, reduces liquid steel pollution, enhances operational safety and equipment service life, reduces inclusions in the steel billet, and reduces production costs.
Smart Images

Figure CN119282094A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of steelmaking continuous casting, and particularly relates to tundish drainage sand and a preparation method thereof. Background Art
[0002] The tundish non-stopper controlled flow pouring method is one of the important operating methods in the production process of small-section billet casting. This method does not require a stopper rod or a stopper rod control mechanism, and controls the molten steel flow rate through the sizing nozzle to stabilize the billet drawing speed. Compared with the stopper controlled flow pouring method, it has the following advantages: through the continuous optimization of raw material matching and manufacturing process, the service life of the sizing nozzle, one of the main consumable continuous casting functional refractory materials, has been greatly improved, and the number of continuous casting furnaces and the molten steel yield of the casting machine have been greatly improved; at the same time, the sizing nozzle controls the molten steel flow rate relatively stably, and the molten steel has a high cleanliness, which is conducive to improving the quality of continuous casting billets. The cost of tundish refractory materials and equipment spare parts is low, which reduces the overall continuous casting production cost.
[0003] The stopper-free controlled flow pouring method requires flow blocking before pouring. That is, before the tundish is baked, blind plates and blocking cones are installed in each water inlet in turn to block the lower mouth of the slider, and then common metallurgical auxiliary materials on site, such as continuous casting protection slag or ladle drainage sand, are added to the sizing nozzle. After 3-8 hours of variable temperature baking in the temperature range of 600-1100℃, the tundish stores steel for 4-8 minutes when pouring. After the molten steel reaches a certain height (volume), the blocking cones and blind plates are removed, and the pouring slider is replaced. The outflowing protection slag or drainage sand materials are collected and removed, and casting begins. However, this operation mode has the following problems: the protective slag materials filled in the sizing nozzle are mostly designed for steel pouring lubrication with a melting point of 1000-1100℃. A large amount of them have been melted and agglomerated during the baking process of the tundish. In addition, the high-temperature molten steel intensifies the sintering during the steel storage process in the tundish, blocking the nozzle channel. In most cases, the molten steel cannot flow out automatically when pouring begins, and oxygen drainage is required; the drainage sand filled in the sizing nozzle is mainly designed for the long heat load time of the ladle, with high refractoriness. The initial sintering temperature is mostly above 1550℃, and there is basically no over-sintering during the baking and steel storage of the tundish. However, due to the small space at the bottom of the tundish, in the initial stage of steel pouring from the ladle to the tundish, the steel flow impacts the vortex area and almost covers the entire bottom of the ladle. The drainage sand that has not formed a sintered layer in time will be quickly washed away and floated in the molten steel. Casting will start a few minutes later. At this time, the drainage sand floating in the molten steel has not yet completed floating, and is poured into the ingot with the steel flow, causing harmful inclusions. There is also a part of drainage sand in the nozzle that forms a steel-sand mixture due to the mixing of molten steel, which blocks the nozzle channel and has a higher probability of oxygen burning and drainage.
[0004] Furthermore, the oxygen burning and drainage during the pouring of the tundish is very harmful, including: 1. It causes peroxidation pollution of the molten steel; 2. There are safety hazards of burns and scalds in the oxygen burning process; 3. The high-temperature and high-pressure oxygen lance jet will damage the zirconium layer on the inner wall of the sizing nozzle, thereby causing the inner diameter of the sizing nozzle to expand too quickly, reducing the service life of the tundish and the number of continuous casting furnaces, affecting production efficiency and production cost control.
[0005] At present, there is little research and development on special filling materials for the sizing nozzle of the tundish. The patent document with publication number CN118305286A provides a method for automatic pouring of continuous casting sizing nozzle casting. Before the tundish is blocked, the asbestos rope is rolled into strips according to the aperture of the slider, plugged into the upper mouth of the tundish upper nozzle toward the lower mouth of the slider, and a small amount of protective slag is added to the remaining part of the upper mouth of the tundish upper nozzle to fill it flush. One end of the asbestos rope passes through the slider 30-50mm, and the asbestos rope is manually pulled to drain when pouring. This method has the following shortcomings in actual production and use: 1. The problem of sintering of the upper protective slag still exists; 2. The asbestos rope contacts the high-temperature molten steel during the storage of steel in the tundish, the yarn is easily burned and broken, and the reliability of pulling and draining is not high; 3. Asbestos products are one of the primary targets of environmental pollution control in current production phenomena, which are extremely harmful to the health of workers and the probability of use should be reduced as much as possible.
[0006] Therefore, the applicant believes that there is an urgent need to develop a drainage sand product for filling the sizing nozzle of the tundish, which has a high pouring rate, little pollution to the molten steel, is easy to use on site and is safe. Summary of the invention
[0007] In view of this, the technical problem to be solved by the present invention is to provide a tundish drainage sand for the deficiencies in the prior art, which is suitable for the plug-free flow controlled pouring method, improves the automatic pouring rate, and reduces the pollution of molten steel.
[0008] In order to solve the above technical problems, the technical solution adopted by the present invention is: A tundish drainage sand is made of magnesite sand, dolomite sand, raw perlite, kyanite, rare earth mineral powder and a binder, wherein the weight proportion of the magnesite sand is 40-60 parts, the weight proportion of the dolomite sand is 15-35 parts, the weight proportion of the raw perlite is 10-30 parts, the weight proportion of the kyanite is 5-15 parts, the weight proportion of the rare earth mineral powder is 2-5 parts, and the weight proportion of the binder is 1-3 parts.
[0009] Preferably, the weight percentage of MgO contained in the magnesite sand is ≥45%, the weight percentage of loss on ignition is ≥50%, and the particle size is 0.3 mm-1.5 mm.
[0010] Preferably, the dolomite sand contains CaO in a weight percentage of ≥30%, MgO in a weight percentage of ≥20%, loss on ignition in a weight percentage of ≥40%, and a particle size of 0.3 mm-1.5 mm.
[0011] Preferably, the raw pearlite contains SiO2 in an amount of ≥70% by weight, Al2O3 in an amount of ≥12% by weight, has a particle size of 0.3 mm to 1.5 mm, and has an expansion multiple of ≥15 times at 1300°C.
[0012] Preferably, the kyanite contains Al2O3 in an amount of ≥60% by weight, SiO2 in an amount of ≥35% by weight, has a particle size of 0.3 mm to 1.5 mm, and an expansion rate at 1100°C of ≥18%.
[0013] Preferably, the weight percentage of REO in the rare earth ore powder is ≥70%, REO is a combination of one or more components of La2O3, CeO2, Nd2O3 and Y2O3, and the particle size is -200 mesh.
[0014] Preferably, the adhesive is liquid water glass with a modulus of 2.0-3.2.
[0015] Preferably, the mass percentage of the effective ingredients of the tundish drainage sand is: MgO: 21.0%-32.0%, SiO2: 9.0%-26.0%, CaO: 4.5%-11.0%, Al2O3: 4.3%-13.0%, REO: 1.4%-4.0%, loss on ignition: 26%-40%, and the rest are unavoidable impurities.
[0016] A method for preparing tundish drainage sand comprises the following steps: S1: providing raw perlite, kyanite and a binder, stirring and mixing, then adding rare earth mineral powder, and continuing to stir to obtain particles covered with rare earth mineral powder; S2: drying the granules covered with rare earth mineral powder, wherein the moisture content of the dried product is less than 0.1%, and a dry granule product is obtained; S3: mixing the dry granular product with magnesite sand and dolomite sand, stirring to obtain a semi-finished product; S4: Screen the semi-finished product, take the material on the sieve, and obtain the product.
[0017] Preferably, the air supply temperature of the drying process is 200°C-450°C.
[0018] Preferably, the sieve mesh size of the screening is 60 mesh.
[0019] A method for using tundish drainage sand comprises: before the tundish is baked, adding the sand into each injection and sizing nozzle of the tundish, wherein the amount of sand added is based on whether the nozzle is full or slightly overflows the nozzle.
[0020] The tundish drainage sand developed by the present invention is greatly different from the conventional ladle drainage sand in terms of functional requirements, which is specifically manifested in that the ladle drainage sand has a long heat load time and needs to withstand the ablation of high-temperature molten steel for a long time. Usually, the refractoriness is given priority, followed by the sintering speed, so as to delay the functional effect loss caused by the molten steel flushing and floating during the molten steel circulation treatment. The heat load time of the tundish drainage sand is divided into two parts. The first part is the tundish baking period, which needs to achieve the effect of removing the water content of the ladle wall castable and preheating the tundish. Although the duration is long, the temperature is relatively low (600-1100℃). The second part is the steel storage period before the tundish starts casting, which is mostly within 10 minutes. Therefore, the sintering problem of the tundish drainage sand is usually not serious. The main problem is that the bottom of the tundish is narrow and the steel flow impact is serious, resulting in the phenomenon of not being able to start pouring automatically; in addition, the tundish liquid level is shallow, and the static pressure of the molten steel is much smaller than that of the ladle. Therefore, the compressive strength of the sintered material of the tundish drainage sand must be small, so that it is possible to achieve an increase in the automatic pouring rate.
[0021] Compared with the prior art, the present invention has the following beneficial effects: Based on the above technical solution, the present invention provides a tundish drainage sand, which is suitable for a plug-free flow-controlled casting method, improves the automatic pouring rate of the tundish, reduces molten steel pollution, and is safe to operate and highly reliable.
[0022] The magnesite sand and dolomite sand used in the tundish drainage sand of the present invention decompose at 700-900°C to release CO2 gas, which is discharged together with the water vapor in the tundish castable to form porous, lightweight particles with low compressive strength and low pulverization rate; raw perlite and kyanite produce obvious volume expansion at the heat load temperature to generate lightweight materials, and form a certain amount of liquid phase at about 1000°C to adhere the drainage sand particles to prevent excessive scouring and floating of molten steel. The porous particles with low compressive strength generated by the compounding of the above materials can effectively improve the automatic pouring rate.
[0023] The products of the magnesite sand, dolomite sand, raw perlite and kyanite used in the present invention are all lightweight materials at the temperature in the tundish, and can quickly float to the surface of the molten steel during the limited steel storage period in the tundish, thereby reducing the inclusion of the molten steel. In addition, the high alkaline components of MgO and CaO generated by the high-temperature decomposition of magnesite sand and dolomite sand will not pollute the molten steel for the second time; raw perlite and kyanite contain acidic SiO2 components, and the surface of their particles is stably coated with rare earth mineral powder by a binder, which can minimize the redox reaction with the alloy components in the molten steel during the inevitable and short floating process in the tundish, thereby avoiding the pollution of the molten steel.
[0024] The drainage sand of the present invention is specifically designed according to the operation characteristics of the tundish and the heat load temperature. During the baking period of the tundish, part of the raw materials are heated to precipitate a certain amount of liquid phase, and light adhesion occurs between the drainage sand particles to form a sand shell of certain strength. When the ladle pours steel into the tundish, the impact of the steel flow and the floating sand mounds are alleviated, the number of floating sand particles is reduced, the inclusion phenomenon of molten steel is reduced, and the automatic pouring rate of each injection flow of the tundish is improved.
[0025] The drainage sand of the present invention will undergo crystal phase transformation or composition change when heated during the baking and steel storage in the tundish, resulting in volume expansion and generating low-density particles. For the inevitable floating part, the floating speed can be accelerated and it is easier to be captured by the tundish covering agent within the limited steel storage time in the tundish, thereby reducing the pollution of molten steel and the inclusion problem of the ingot and improving the purity of the molten steel.
[0026] The raw materials of the drainage sand of the present invention can be divided into two categories according to their components: one is a highly alkaline material containing MgO and CaO components, which is oxygen-affinity and has strong stability; the other is an acidic raw material containing SiO2 components, which can adjust the sintering temperature and / or strength. For the latter raw materials, a stable coating treatment is performed on the outer layer of the particles, and during the inevitable and short floating process in the tundish, the redox reaction with the alloy components in the molten steel can be reduced to the greatest extent to avoid contaminating the molten steel. In this way, while ensuring smooth and automatic pouring, the influence of molten steel pollution and ingot inclusion problems on the quality of steel is significantly reduced.
[0027] For long process steps of multi-furnace continuous casting, as the operation time is prolonged, the amount of refractory lining peeling of each related equipment gradually increases. In addition, the original inclusions in the molten steel are gradually enriched at the interface between the molten steel surface and the covering agent. If the total amount of enrichment is too high, it will cause the covering agent slag system to change and cause molten steel pollution at the interface. For the drainage sand of the present invention, after the ladle pours steel into the tundish, the unavoidable floating part will be gradually captured by the covering agent. Because its main components are high-alkalinity MgO and CaO components, the covering agent's adsorption capacity for SiO2 and Al2O3 inclusions can be enhanced. The drainage sand of the present invention contains a small amount of REO component, which is a strong promoter of the sulfur and phosphorus fixation effects in steel slag, and also plays a positive role in promoting the purification of molten steel. DETAILED DESCRIPTION
[0028] In order to better understand the present invention, the content of the present invention is further clearly set forth in conjunction with the embodiments below, but the protection content of the present invention is not limited to the following embodiments. In the following description, a large number of specific details are provided in order to provide a more thorough understanding of the present invention. However, it is obvious to those skilled in the art that the present invention can be implemented without one or more of these details.
[0029] Unless otherwise specified, all raw materials are from commercially available products and do not contain other unspecified components except inevitable impurities unless otherwise specified.
[0030] In the following implementation cases, the weight percentage of MgO contained in the magnesite sand is ≥45%, the weight percentage of loss on ignition is ≥50%, and the particle size is 0.3 mm-1.5 mm.
[0031] The weight percentage of CaO contained in dolomite sand is ≥30%, the weight percentage of MgO is ≥20%, the weight percentage of loss on ignition is ≥40%, and the particle size is 0.3mm-1.5mm.
[0032] The raw pearlite contains SiO2 at a weight percentage of ≥70%, Al2O3 at a weight percentage of ≥12%, a particle size of 0.3mm-1.5mm, and an expansion multiple of ≥15 times at 1300°C.
[0033] The weight percentage of Al2O3 contained in kyanite is ≥60%, the weight percentage of SiO2 contained in kyanite is ≥35%, the particle size is 0.3mm-1.5mm, and the expansion rate at 1100℃ is ≥18%.
[0034] The adhesive is liquid water glass with a modulus of 2.0-3.2.
[0035] In the following examples and comparative examples, the sum of parts by weight of each raw material is 100 parts by weight.
[0036] Example 1: A tundish drainage sand is made of magnesite sand, dolomite sand, raw perlite, kyanite, rare earth mineral powder and a binder, wherein the weight proportion of the magnesite sand is 50 parts, the weight proportion of the dolomite sand is 20 parts, the weight proportion of the raw perlite is 15 parts, the weight proportion of the kyanite is 10 parts, the weight proportion of the rare earth mineral powder is 3 parts, and the weight proportion of the binder is 2 parts.
[0037] The weight percentage of REO contained in the rare earth ore powder is ≥70%, REO is La2O3 and CeO2, and the particle size is -200 mesh.
[0038] The mass percentage of effective ingredients in the tundish drainage sand is: MgO: 27.04%, SiO2: 14.29%, CaO: 6.12%, Al2O3: 7.96%, REO: 2.14%, loss on ignition: 33%, and the rest are unavoidable impurities.
[0039] A method for preparing tundish drainage sand comprises the following steps: S1: providing raw perlite, kyanite and a binder, stirring and mixing, then adding rare earth mineral powder, and continuing to stir to obtain particles covered with rare earth mineral powder; S2: drying the granules covered with rare earth mineral powder, wherein the moisture content of the dried product is less than 0.1%, and a dry granule product is obtained; S3: mixing the dry granular product with magnesite sand and dolomite sand, stirring to obtain a semi-finished product; S4: Screen the semi-finished product, take the material on the sieve, and obtain the product.
[0040] The air supply temperature for the drying process is 350°C.
[0041] The sieve aperture for screening is 60 mesh.
[0042] Example 2: A tundish drainage sand is made of magnesite sand, dolomite sand, raw perlite, kyanite, rare earth mineral powder and a binder, wherein the weight proportion of the magnesite sand is 47 parts, the weight proportion of the dolomite sand is 15 parts, the weight proportion of the raw perlite is 30 parts, the weight proportion of the kyanite is 5 parts, the weight proportion of the rare earth mineral powder is 2 parts, and the weight proportion of the binder is 1 part.
[0043] The weight percentage of REO contained in the rare earth ore powder is ≥70%, REO is La2O3 and Nd2O3, and the particle size is -200 mesh.
[0044] The mass percentage of effective ingredients in the tundish drainage sand is: MgO: 24.39%, SiO2: 22.98%, CaO: 4.55%, Al2O3: 6.67%, REO: 1.41%, loss on ignition: 29.5%, and the rest are unavoidable impurities.
[0045] A method for preparing tundish drainage sand comprises the following steps: S1: providing raw perlite, kyanite and a binder, stirring and mixing, then adding rare earth mineral powder, and continuing to stir to obtain particles covered with rare earth mineral powder; S2: drying the granules covered with rare earth mineral powder, wherein the moisture content of the dried product is less than 0.1%, and a dry granule product is obtained; S3: mixing the dry granular product with magnesite sand and dolomite sand, stirring to obtain a semi-finished product; S4: Screen the semi-finished product, take the material on the sieve, and obtain the product.
[0046] The air supply temperature for the drying process is 200°C.
[0047] The sieve aperture for screening is 60 mesh.
[0048] Example 3: A tundish drainage sand is made of magnesite sand, dolomite sand, raw perlite, kyanite, rare earth mineral powder and a binder, wherein the weight proportion of the magnesite sand is 52 parts, the weight proportion of the dolomite sand is 18 parts, the weight proportion of the raw perlite is 12 parts, the weight proportion of the kyanite is 15 parts, the weight proportion of the rare earth mineral powder is 2 parts, and the weight proportion of the binder is 1 part.
[0049] The weight percentage of REO in the rare earth ore powder is ≥70%, REO is Y2O3, and the particle size is -200 mesh.
[0050] The mass percentage of effective ingredients in the tundish drainage sand is: MgO: 27.27%, SiO2: 13.79%, CaO: 5.45%, Al2O3: 10.55%, REO: 1.41%, loss on ignition: 33.2%, and the rest are unavoidable impurities.
[0051] A method for preparing tundish drainage sand comprises the following steps: S1: providing raw perlite, kyanite and a binder, stirring and mixing, then adding rare earth mineral powder, and continuing to stir to obtain particles covered with rare earth mineral powder; S2: drying the granules covered with rare earth mineral powder, wherein the moisture content of the dried product is less than 0.1%, and a dry granule product is obtained; S3: mixing the dry granular product with magnesite sand and dolomite sand, stirring to obtain a semi-finished product; S4: Screen the semi-finished product, take the material on the sieve, and obtain the product.
[0052] The air supply temperature for the drying process is 450°C.
[0053] The sieve aperture for screening is 60 mesh.
[0054] Example 4: A tundish drainage sand is made of magnesite sand, dolomite sand, raw perlite, kyanite, rare earth mineral powder and a binder, wherein the weight proportion of the magnesite sand is 45 parts, the weight proportion of the dolomite sand is 35 parts, the weight proportion of the raw perlite is 10 parts, the weight proportion of the kyanite is 5 parts, the weight proportion of the rare earth mineral powder is 2 parts, and the weight proportion of the binder is 3 parts.
[0055] The weight percentage of REO in the rare earth ore powder is ≥70%, REO is CeO2, and the particle size is -200 mesh.
[0056] The mass percentage of effective ingredients in the tundish drainage sand is: MgO: 28.09%, SiO2: 9.02%, CaO: 10.82%, Al2O3: 4.33%, REO: 1.44%, loss on ignition: 36.5%, and the rest are unavoidable impurities.
[0057] The preparation method of the tundish drainage sand is as shown in Example 1.
[0058] Example 5: A tundish drainage sand is made of magnesite sand, dolomite sand, raw perlite, kyanite, rare earth mineral powder and a binder, wherein the weight proportion of the magnesite sand is 55 parts, the weight proportion of the dolomite sand is 17 parts, the weight proportion of the raw perlite is 12 parts, the weight proportion of the kyanite is 8 parts, the weight proportion of the rare earth mineral powder is 5 parts, and the weight proportion of the binder is 3 parts.
[0059] The weight percentage of REO in the rare earth ore powder is ≥70%, REO is Nd2O3, and the particle size is -200 mesh.
[0060] The mass percentage of effective ingredients in the tundish drainage sand is: MgO: 29.02%, SiO2: 11.55%, CaO: 5.26%, Al2O3: 6.43%, REO: 3.61%, loss on ignition: 34.3%, and the rest are unavoidable impurities.
[0061] The preparation method of the tundish drainage sand is as shown in Example 1.
[0062] Example 6: A tundish drainage sand is made of magnesite sand, dolomite sand, raw perlite, kyanite, rare earth mineral powder and a binder, wherein the weight proportion of the magnesite sand is 40 parts, the weight proportion of the dolomite sand is 22 parts, the weight proportion of the raw perlite is 23 parts, the weight proportion of the kyanite is 12 parts, the weight proportion of the rare earth mineral powder is 2 parts, and the weight proportion of the binder is 1 part.
[0063] The weight percentage of REO in the rare earth ore powder is ≥70%, REO is La2O3, and the particle size is -200 mesh.
[0064] The mass percentage of effective ingredients in the tundish drainage sand is: MgO: 22.63%, SiO2: 20.51%, CaO: 6.67%, Al2O3: 10.06%, REO: 1.41%, loss on ignition: 28.8%, and the rest are unavoidable impurities.
[0065] The preparation method of the tundish drainage sand is as shown in Example 1.
[0066] Example 7: A tundish drainage sand is made of magnesite sand, dolomite sand, raw perlite, kyanite, rare earth mineral powder and a binder, wherein the weight proportion of the magnesite sand is 60 parts, the weight proportion of the dolomite sand is 15 parts, the weight proportion of the raw perlite is 16 parts, the weight proportion of the kyanite is 6 parts, the weight proportion of the rare earth mineral powder is 2 parts, and the weight proportion of the binder is 1 part.
[0067] The weight percentage of REO contained in the rare earth ore powder is ≥70%, REO is La2O3, CeO2 and Nd2O3, and the particle size is -200 mesh.
[0068] The mass percentage of effective ingredients in the tundish drainage sand is: MgO: 30.30%, SiO2: 13.43%, CaO: 4.55%, Al2O3: 5.58%, REO: 1.41%, loss on ignition: 36%, and the rest are unavoidable impurities.
[0069] The preparation method of the tundish drainage sand is as shown in Example 1.
[0070] Comparative Example 1: A tundish drainage sand, which is different from Example 1 in that magnesia sand is used instead of magnesite sand, and the weight percentage of MgO contained in the magnesia sand is ≥90%, and the other components are the same as those in Example 1. The mass percentages of the effective components of the tundish drainage sand are: MgO: 50%, SiO2: 14.29%, CaO: 6.12%, Al2O3: 7.96%, REO: 2.14%, ignition loss: 8%, and the rest are unavoidable impurities.
[0071] Comparative Example 2: A tundish drainage sand, which is different from Example 1 in that limestone is used instead of dolomite sand, the weight percentage of CaO in the limestone is ≥50%, the loss on ignition is ≥40%, and the other components are the same as those in Example 1. The mass percentages of the effective components of the tundish drainage sand are: MgO: 22.96%, SiO2: 14.29%, CaO: 10.20%, Al2O3: 7.96%, REO: 2.14%, loss on ignition: 33%, and the rest are unavoidable impurities.
[0072] Comparative Example 3: A tundish drainage sand, which is different from Example 1 in that expanded perlite is used instead of raw perlite, and the weight percentage of SiO2 contained in the expanded perlite is ≥70%, and the weight percentage of Al2O3 contained in the expanded perlite is ≤15%. The mass percentages of the effective components of the tundish drainage sand are: MgO: 27.04%, SiO2: 14.29%, CaO: 6.12%, Al2O3: 8.42%, REO: 2.14%, ignition loss: 33%, and the rest are unavoidable impurities.
[0073] Comparative Example 4: A tundish drainage sand is made of magnesite sand, dolomite sand, raw perlite, kyanite, rare earth ore powder and a binder, wherein the weight of magnesite sand is 70 parts, the weight of dolomite sand is 10 parts, the weight of raw perlite is 10 parts, the weight of kyanite is 5 parts, the weight of rare earth ore powder is 4 parts, and the weight of the binder is 1 part. The weight percentage of REO contained in the rare earth ore powder is ≥70%, and REO is La2O3 and CeO2, with a particle size of -200 mesh. The mass percentage of the effective components of the tundish drainage sand is: MgO: 33.84%, SiO2: 8.84%, CaO: 3.03%, Al2O3: 4.24%, REO: 2.83%, ignition loss: 39%, and the rest are unavoidable impurities. The preparation method thereof refers to Example 1.
[0074] Comparative Example 5: A tundish drainage sand is made of magnesite sand, dolomite sand, raw perlite, kyanite, rare earth ore powder and binder, the weight of magnesite sand is 20 parts, the weight of dolomite sand is 15 parts, the weight of raw perlite is 40 parts, the weight of kyanite is 20 parts, the weight of rare earth ore powder is 3 parts, and the weight of binder is 2 parts. The weight percentage of REO contained in the rare earth ore powder is ≥70%, REO is La2O3 and CeO2, and the particle size is -200 mesh. The mass percentage of the effective ingredients of the tundish drainage sand is: MgO: 12.44%, SiO2: 35.49%, CaO: 4.74%, Al2O3: 17.36%, REO: 2.14%, ignition loss: 16.37%, and the rest are unavoidable impurities. The preparation method thereof refers to Example 1.
[0075] Comparative Example 6: The difference from Example 1 is that the binder is omitted; accordingly, the step of adding the binder is omitted in the preparation method of the tundish drainage sand. A tundish drainage sand is made of magnesite sand, dolomite sand, raw perlite, kyanite and rare earth ore powder, wherein the weight proportion of magnesite sand is 51 parts, the weight proportion of dolomite sand is 20.4 parts, the weight proportion of raw perlite is 15.3 parts, the weight proportion of kyanite is 10.2 parts, and the weight proportion of rare earth ore powder is 3.1 parts. The mass percentage of the effective ingredients in the tundish drainage sand is: MgO: 27.03%, SiO2: 14.28%, CaO: 6.12%, Al2O3: 8.42%, REO: 2.17%, ignition loss: 33.7%, and the rest are unavoidable impurities.
[0076] Comparative Example 7: The difference from Example 1 is that rare earth ore powder is omitted; accordingly, the step of adding rare earth ore powder is omitted in the preparation method of tundish drainage sand. A tundish drainage sand is made of magnesite sand, dolomite sand, raw perlite, kyanite and a binder, wherein the weight proportion of magnesite sand is 51.5 parts, the weight proportion of dolomite sand is 20.6 parts, the weight proportion of raw perlite is 15.5 parts, the weight proportion of kyanite is 10.3 parts, and the weight proportion of the binder is 2.1 parts. The mass percentage of the effective ingredients of the tundish drainage sand is: MgO: 27.88%, SiO2: 14.77%, CaO: 6.31%, Al2O3: 8.69%, REO: 0%, ignition loss: 34.0%, and the rest are unavoidable impurities.
[0077] The above-mentioned method of using the tundish drainage sand is to add it into each injection and sizing nozzle of the tundish before the tundish is baked, and the amount added is based on the filling of the nozzle.
[0078] Effect evaluation case: 1. The drainage sand prepared in Examples 1-7 and Comparative Examples 1-7 was applied to a steel plant in Handan, with a tundish capacity of 35t and an 8-stream sizing nozzle. The average self-opening rate of each drainage sand was statistically expressed in "%", as shown in Table 1.
[0079] 2. To evaluate the effect of drainage sand on inclusions in molten steel, three batches of drainage sand produced by Examples 1-7 and Comparative Examples 1-7 were randomly selected for inclusion detection. The inclusions in the billet samples were analyzed using a scanning electron microscope and a large area energy dispersive spectrometer, and the sizes of the inclusions were classified. The number of inclusions of different sizes was counted and graded according to GB / T10561. The test results were averaged and integers were retained. The average value was expressed as "pieces / cm 2 The statistical results are shown in Table 1.
[0080] 3. In order to evaluate the degree of redox reaction of alloy components in molten steel by different drainage sand components, three batches were randomly selected. During the casting of steel in the tundish, samples of molten steel were taken at a depth of about 100 mm or more below the covering agent. The loss of alloy elements represented by [Als] was detected using the drainage sand produced in Examples 1-7 and Comparative Examples 1-7. The loss was displayed as the difference between the [Als] content of the molten steel at the station and the [Als] content of the tundish sample. The test results were averaged and expressed in "ppm". The statistical results are shown in Table 1.
[0081] Table 1 Statistical results of self-opening rate, number of inclusions and [Als] loss The above statistical results show that: (1) The average self-opening rate of the tundish drainage sand of the present invention is above 91.0%, which is significantly improved to varying degrees compared with Comparative Examples 1-7.
[0082] (2) The number of inclusions of different sizes in the steel billet produced by the tundish drainage sand of the present invention is different, among which the number of inclusions of 2-5 μm is the largest, followed by the number of inclusions of 1-2 μm, and the number of DS inclusions ≥13 μm is the smallest, which is basically the same as the rule of comparative examples 1-7. However, the number of DS inclusions in comparative examples 1, 3 and 6-7 is significantly increased compared with that in the present invention, and other sizes are also more than that in the present invention. The number of inclusions in comparative examples 2 and 4-5 is not significantly changed compared with that in the present invention.
[0083] (3) After the tundish drainage sand of the present invention is captured by the covering agent, the molten steel at a depth of more than 100 mm is sampled and tested, and the average [Als] loss is 1.03 ppm. The [Als] loss of Comparative Examples 1-4 is higher than that of the present invention, all of which are above 1.4 ppm; the [Als] loss of Comparative Examples 5-7 is significantly higher than that of the present invention, all reaching above 3.7 ppm. It can be seen that the adverse effects of Comparative Examples 1-7 on the target composition and quality requirements of steel are more significant.
[0084] The above results show that the synergistic effect of raw material selection and matching in the present invention is more significant, which not only helps to improve the self-opening rate of the ladle at the sizing nozzle, but also helps to reduce the size and number of inclusions in the molten steel, improve the quality of steel grades, and has low reactivity to alloy elements represented by [Als] in the molten steel, with low loss, and well takes into account the actual needs of the tundish self-opening and molten steel purification.
[0085] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Other modifications or equivalent substitutions made to the technical solution of the present invention by ordinary technicians in the field should be included in the scope of the claims of the present invention as long as they do not depart from the spirit and scope of the technical solution of the present invention.
Claims
1. A tundish drainage sand, characterized in that: The invention is made of magnesite sand, dolomite sand, raw perlite, kyanite, rare earth ore powder and a binder, wherein the weight proportion of the magnesite sand is 40-60 parts, the weight proportion of the dolomite sand is 15-35 parts, the weight proportion of the raw perlite is 10-30 parts, the weight proportion of the kyanite is 5-15 parts, the weight proportion of the rare earth ore powder is 2-5 parts, and the weight proportion of the binder is 1-3 parts.
2. The tundish drainage sand according to claim 1, characterized in that: The weight percentage of MgO contained in the magnesite sand is ≥45%, the weight percentage of loss on ignition is ≥50%, and the particle size is 0.3 mm-1.5 mm.
3. The tundish drainage sand according to claim 2, characterized in that: The dolomite sand contains CaO in a weight percentage of ≥30%, MgO in a weight percentage of ≥20%, loss on ignition in a weight percentage of ≥40%, and a particle size of 0.3 mm-1.5 mm.
4. The tundish drainage sand according to claim 3, characterized in that: The raw pearlite contains SiO2 in a weight percentage of ≥70%, Al2O3 in a weight percentage of ≥12%, a particle size of 0.3 mm-1.5 mm, and an expansion multiple of ≥15 times at 1300°C.
5. The tundish drainage sand according to claim 4, characterized in that: The kyanite contains Al2O3 in an amount of ≥60% by weight, SiO2 in an amount of ≥35% by weight, a particle size of 0.3 mm to 1.5 mm, and an expansion rate of ≥18% at 1100°C.
6. The tundish drainage sand according to claim 5, characterized in that: The weight percentage of REO contained in the rare earth ore powder is ≥70%, REO is a combination of one or more components of La2O3, CeO2, Nd2O3 and Y2O3, and the particle size is -200 mesh.
7. The tundish drainage sand according to claim 6, characterized in that: The adhesive is liquid water glass with a modulus of 2.0-3.
2.
8. The tundish drainage sand according to claim 7, characterized in that: The mass percentage of the effective components of the tundish drainage sand is: MgO: 21.0%-32.0%, SiO2: 9.0%-26.0%, CaO: 4.5%-11.0%, Al2O3: 4.3%-13.0%, REO: 1.4%-4.0%, ignition loss: 26%-40%, and the rest are inevitable impurities.
9. A method for preparing tundish drainage sand according to any one of claims 1 to 8, characterized in that: The following steps are involved: S1: providing raw perlite, kyanite and a binder, stirring and mixing, then adding rare earth mineral powder, and continuing to stir to obtain particles covered with rare earth mineral powder; S2: drying the granules covered with rare earth mineral powder, wherein the moisture content of the dried product is less than 0.1%, and a dry granule product is obtained; S3: mixing the dry granular product with magnesite sand and dolomite sand, stirring to obtain a semi-finished product; S4: Screen the semi-finished product, take the material on the sieve, and obtain the product.
10. A method for using the tundish drainage sand according to any one of claims 1 to 9, characterized in that: include: Before the tundish is baked, add it to each injection and sizing nozzle of the tundish, and the amount added should be based on whether the nozzle is full or slightly overflowing.
Citation Information
Patent Citations
Automatic casting method for continuous casting sizing nozzle casting
CN118305286A
Cited By
Method for improving automatic tapping rate of high-temperature ladle by using rare earth modified channel sand
CN122702949A
Method for improving automatic tapping rate of high-temperature ladle by using rare earth modified channel sand
CN122702949B